Persepsi Peserta Didik Terhadap Penggunaan Media Pembelajaran Di SMPN 3 Painan - Loli Setriani; Slamet Rianto; Trina Febriani (Departement of Mathematics Education, 2023)
This study aims to find out students about learning media. This study used qualitative research methods. The data source for this research came from interviews with 1 teacher and 4 students at SMPN 3 Painan, while the methods used in data collection techniques were interviews, observation, and documentation. With this method it is expected to obtain the data needed in the research, so as to obtain concrete data that fits the needs of the research conducted at SMPN 3 Painan. The subjects of this study were students at SMPN 3 Painan. The results of this study, both from the results of interviews and observations made during research at SMPN 3 Painan, show that the use of instructional media in class was well planned by the teacher concerned. The use of learning media used by the teacher is not only on one daily test, midterm or even the end of the semester but the teacher always uses learning media in every learning process. The use of learning media is very important and good to apply in classroom learning, because using learning media is more developed on technological issues. Then the media used is in accordance with learning because it is taken from the internet and books. While the perception of students in the use of learning media is the perception of the use of learning media that can describe something abstract in accordance with their experiences during learning. Students understand more about learning not only verbally because a lot of material is only verbalistic, and the teacher only explains it, using the media the teacher can describe something abstract, not just explain it, so that students really understand learning